Halal certification facilitation for value addition of lemang as a regional culinary identity of Malingping, Lebak Regency - Zakaria, Zakaria; Hidayati, Rahmi; Mahpudin, Mahpudin (Community Empowerment, 2025)
As a Muslim-majority country, Indonesia has made halal product assurance a central policy to promote global halal tourism and strengthen its national identity. The government, through the Halal Product Assurance Organizing Agency (BPJPH), has mandated halal certification for all businesses. To accelerate this, a free halal certification program has been launched, specifically targeting micro, small, and medium enterprises (MSMEs). However, this program remains largely unknown, especially in rural and peripheral areas like Malingping, Lebak Regency. This community service initiative aimed to assist local Nasi Lemang producers in Malingping, South Lebak, in obtaining halal certification. Many of these entrepreneurs lack the necessary knowledge about the procedures and requirements for certification. The method employed involved a combination of socialization, mentoring, and technical assistance throughout the halal certification registration process. The outcome of this program was the successful acquisition of halal certificates by the Nasi Lemang entrepreneurs. This not only ensures their products comply with national standards but also enhances the added value of Lemang as a distinctive culinary icon of Malingping. Ultimately, this effort contributes to the preservation of local culinary heritage while supporting Indonesia's broader halal industry development agenda.